Pembaharuan status, pencitraan personal, kepercayaan dan keputusan pembelian daring - Adi Kurnia Djarot Nahusona; Roos Kities Andadari (Jurnal Ekonomi dan Bisnis, 2018)
One of the most popular mobile messaging application in Indonesia is Blackberry Messenger. This application is not only popular for facilitating daily interactions but also commercial activities. In this respect, RF Shop as an e-commerce firm has utilized the status updating feature offered by Blackberry Messenger for their marketing activities. Specifically, this firm regularly updates its religious messages in its Blackberry Messenger status as a part of its personal branding. Thus, this research aims to test the effects of updating religious message in its Blackberry Messenger status as the seller’s personal branding on purchasing decisions in the e-commerce environment. This study uses a quantitative approach by distributing email-based questionnaires to 280 RF Shop’s customers with 115 completed questionnaires. Using the Partial Least Square (PLS), this study demonstrates status updating affects the seller’s personal branding. Further, a well-designed seller’s personal branding by updating religious messages positively affects customers’ trust. Eventually, customers’ trust will affect their decisions in the e-commerce environment.